2017
DOI: 10.1016/j.carpath.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial remodeling, hypertrophy, and fibrosis in mouse models of heart failure

Abstract: Left ventricular dysfunction increases left atrial pressures and causes atrial remodeling. In human subjects, increased left atrial size is a powerful predictor of mortality and adverse events in a broad range of cardiac pathologic conditions. Moreover, structural remodeling of the atrium plays an important role in the pathogenesis of atrial tachyarrhythmias. Despite the potential value of the atrium in assessment of functional endpoints in myocardial disease, atrial pathologic alterations in mouse models of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 50 publications
(57 reference statements)
2
35
0
Order By: Relevance
“…It also develops changes in cardiac structure and function similar to those in T2DM patients . Recent studies have confirmed that functional and morphological alterations in db/db hearts are consistent with DCM …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…It also develops changes in cardiac structure and function similar to those in T2DM patients . Recent studies have confirmed that functional and morphological alterations in db/db hearts are consistent with DCM …”
Section: Introductionmentioning
confidence: 74%
“…16 Recent studies have confirmed that functional and morphological alterations in db/db hearts are consistent with DCM. 17,18 In this study, we aimed to investigate the association of GRK2 with early DCM by estimating the expression of GRKs both in the myocardium of diabetic mice and in the PBMCs of patients with early DCM.…”
Section: Introductionmentioning
confidence: 99%
“…diabetes, obesity female gender and hypertension. Lepr db/db mice were previously shown to display diastolic dysfunction 13,18,19 and to recapitulate significant features of human HFpEF 14,20 . In the present study, we thoroughly characterized the cardiac microvascular phenotype of these mice, notably, via a transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…25 The PV antrum for the PVI in patients with HF may be more thickened compared to that in those without HF because patients with HF have atrial hypertrophy. 15,16 The transmural lesion creation by the PVI may be difficult in patients with HF and the importance of the PVI durability may be emphasized more in those patients.…”
Section: Impact Of the Difference In The Pvi Area And Durability Bementioning
confidence: 99%
“…13,14 However, the underlying pathophysiology differs between patients with and without HF. 15,16 Further, the fundamental mechanism of catheter ablation differs between CB and RF ablation as well. There have been no randomized controlled trials addressing the differences in the clinical outcomes between CB and RF ablation for the treatment of AF in patients with HF.…”
Section: Introductionmentioning
confidence: 99%